Development, Characterization, and Evaluation of Potential Systemic Toxicity of a Novel Oral Melatonin Formulation - Catalina N. Cheaburu-Yilmaz; Kemal Atmaca; Onur Yilmaz; Hilmi Orhan (MDPI AG, 2024)
The need to create safe materials for biomedical and pharmaceutical applications has become a significant driving force for the development of new systems. Therefore, a chitosan-coated copolymer of itaconic acid, acrylic acid, and N-vinyl caprolactam (IT-AA-NVC) was prepared by radical polymerization and subsequent coating via nanoprecipitation to give a system capable of sustained delivery of melatonin. Although melatonin brings undoubted benefits to the human body, aspects of the optimal dose, route, and time of administration for the obtaining of suitable treatment outcomes remain under discussion. The entrapment of melatonin in biocompatible polymeric systems can prevent its oxidation, decrease its toxicity, and provide an increased half-life, resulting in an enhanced pharmacokinetic profile with improved patient compliance. The structures of the biopolymer and conjugate were proven by FTIR, thermal properties were tested by DSC, and the morphologies were followed by SEM. The loading efficiency and in vitro release profile were studied by means of HPLC, and a delayed release profile with an initial burst was obtained. The potential systemic toxicity of the formulation was studied in vivo; a mild hepatotoxicity was observed following administration of the melatonin-loaded formulation to mice, both by histopathology and blood clinical biochemistry. Histopathology showed a mild nephrotoxicity as well; however, kidney clinical biochemistry did not support this.